Design of highly compact reconfigurable filters with tunable reactive loading. (October 2018) - Riaz, Laeeq; Shafique, M. Farhan; Ali, Haider; Naeem, Umair; Khan, Mahmood Ashraf
Abstract: A compact and electronically tunable substrate integrated waveguide cavity resonator is presented in this work. The SIW cavity resonator is loaded symmetrically with stubs on the two sides which are terminated through varactors. By changing the capacitance along the loaded stubs the resonant frequency has been varied. Parametric analyses carried out in this work show a large potential tuning range along with the total resonator size of less than 3/4 λg . The resonator is created on a single layer printed circuit board with integrated biasing network. A two pole filter is realized using the tunable resonator and measured tuning bandwidth of 8.51% at center frequency of 2.55 GHz is demonstrated. The insertion loss is measured between 2.7 and 4.8 dB for the whole range and the return loss is less than 13.5 dB. The technique also allows the real-time fine tuning of coupling coefficient of the two resonators which can easily be extended to the realization of higher order filters. The proposed filter is an excellent candidate for miniaturized RF front-ends where tuning is essential for better spectrum control.